2018
DOI: 10.1093/nar/gky1255
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected diversity in eukaryotic transcription revealed by the retrotransposon hotspot family of Trypanosoma brucei

Abstract: The path from DNA to RNA to protein in eukaryotes is guided by a series of factors linking transcription, mRNA export and translation. Many of these are conserved from yeast to humans. Trypanosomatids, which diverged early in the eukaryotic lineage, exhibit unusual features such as polycistronic transcription and trans-splicing of all messenger RNAs. They possess basal transcription factors, but lack recognisable orthologues of many factors required for transcription elongation and mRNA export. We show that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 99 publications
1
25
0
Order By: Relevance
“…[37]), as well as results from modelling [38], indicate that transcription elongation (figure 2(2)) is usually constitutive. New results from the sequencing of 5-ethynyl uridine-labelled RNA should provide much more detail about transcription initiation and elongation [39].…”
Section: Genome Organization and Transcription In Kinetoplastidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37]), as well as results from modelling [38], indicate that transcription elongation (figure 2(2)) is usually constitutive. New results from the sequencing of 5-ethynyl uridine-labelled RNA should provide much more detail about transcription initiation and elongation [39].…”
Section: Genome Organization and Transcription In Kinetoplastidsmentioning
confidence: 99%
“…The ‘retroposon hotspot’ (RHS) proteins of T. brucei [40] fall into six groups, of which all but RHS6 can be cross-linked to mRNA [41]. By ChIP-Seq, RHS2, RHS4 and RHS6 all colocalize with RNA polymerase II, and RHS6 proteins are directly associated with chromatin [39]. RHS4 and RHS6 proteins are also associated with several other proteins implicated in transcription, whereas RHS2 associates with ribosomes and mRNA-binding proteins [39].…”
Section: Genome Organization and Transcription In Kinetoplastidsmentioning
confidence: 99%
“…Finally, we showed the nuclear location of RHS in the replicative forms of T. cruzi. Although evidence for the functions of RHS in T. cruzi has been elusive, we suggest that these proteins could play a role in modulating the chromatin structure at the transcriptional and posttranscriptional levels, as has been suggested in T. brucei [10,11].…”
Section: The Role Of Rhs Proteins In T Cruzimentioning
confidence: 51%
“…TbRRM, a modulator of the chromatin structure in T. brucei, interacts with RHS transcripts, proteins and histones, suggesting that the RHS family could be involved in chromatin modeling [10]. Recently, it has been reported that several RHS proteins (RHS2, RHS4, and RHS6) may act as factors involved in the transcription elongation and mRNA export in T. brucei [11].…”
Section: The Role Of Rhs Proteins In T Cruzimentioning
confidence: 99%
See 1 more Smart Citation